Odpowiedzi

2010-01-12T15:19:09+01:00
A)3x+4x+5y-2y= 7x + 3y
b)2a-3a+7-6= -1a+1
c)2x-5x+7-x= -4x + 7
d)2a+b-4b= 2a - 3b
e)x-2x+3+x-4= -1
f)3x-y+4x-2y= 7x - 3y
g)2x-6+4x+2= 6x - 4
h)3y-5-5y-6= -2y - 11
i)-2a+2b-3a-3b= -5a - 1b
j)jedna druga t-2x+3t-x-t= 2½t - 3x

Pozdrawiam :)
Najlepsza Odpowiedź!
2010-01-12T15:21:02+01:00
A) 3x+4x+5y-2y=7x+3y
b)2a-3a+7-6=-1a+1
c)2x-5x+7-x=-4x+7
d)2a+b-4b=2a-3b
e)x-2x+3+x-4=-1
f)3x-y+4x-2y=7x-3y
g)2x-6+4x+2=6x-4
h)3y-5-5y-6=-2y-11
i)-2a+2b-3a-3b=-5a-b
j)jedna druga t-2x+3t-x-t=-3x+1 i jedna druga t
zgóry dziękuje !
  • Keyn
  • Początkujący
2010-01-12T15:23:21+01:00
A)7x + 3y
b)-a + 1
c)-4x + 7
d)2a + (-3b)
e)-1
f)7x -3y
g)6x-4
h)-2y-11
j)2 1/2 t - 3x